Eu-Doped Gd2MoB2O9 Phosphors for Latent Fingerprints Detection - N. Chamchoi; N. Sangwaranatee; R. Rajaramakrishna; H. J. Kim; O. Chaemlek; P. Limsuwan; J. Kaewkhao (Integrated ferroelectrics, 2022)
The luminescent powders from rare-earth ions doped oxides have been successfully used for latent fingerprint detection due to high efficiency, high contrast and low background interface. The Gd2MoB2O9:Eu3+ phosphors with varying compositions of Eu3+ions were synthesized by solid state reaction method. These phosphors were investigated by X-ray diffraction (XRD), diffuse reflectance spectroscopy, photoluminescence (PL), and decay curves studies. Multiphoton relaxation decay rate and coupling strength was evaluated using phonon side band spectrum showing 0.4 mol% doped samples show less non radiative decay rate. The 0.40 mol% of Eu3+ ion concentration doped in the Gd2MoB2O9 host lattice show highest photoluminescence emission intensity at 613 nm, in orange red region, monitored at 394 nm excitation. The Gd2MoB2O9:Eu3+ phosphors samples were optimized to 900 °C sintering temperature and optimum milling time at 3 min in the present work. The latent fingerprints detection that developed from Gd2MoB2O9:Eu3+ phosphors in this work exhibited clearly ridge characteristics under UV illumination. The results revealed thatGd2MoB2O9:Eu3+ phosphors are potential practical forensic science applications.
Keywords: Luminescence Properties of Advanced Materials; Forensic Fingerprint Detection Methods; Luminescence and Fluorescent Materials